Voltage-assisted photocatalytic activity of ZnO nanorods grown on carbon fabric for effluent treatment. (10th November 2018) - Sarwar, Zahid; Ashraf, Munir; Rehman, Abdur; Aziz, Humera; Javid, Amjed; Nasir, Nadeem; Iqbal, Kashif; Hussain, Tanveer; Ashar, Ambreen
Abstract: The disposal of colored textile effluent into canals, rivers and sea has adverse effect on aquatic plants and animal life due to reduced penetration of sunlight into water. The aim of this study was to investigate the color removal of textile dyeing effluents with voltage-assisted photocatalytic activity of carbon fabrics containing ZnO nanorods. ZnO nanorods were grown on the oxidized carbon fabric samples by seeding technique using zinc acetate dihydrate and NaOH, followed by hydrothermal process using zinc nitrate hexahydrate (Zn(NO3 )2 ·6H2 O) and hexamethylenetetramine (C6 H12 N4 ). The surface morphology of functionalized carbon fabric was characterized using scanning electron microscope, transmission electron microscope and X-ray diffractometer. It was found that the degradation of dyes in aqueous solutions, with voltage-assisted photocatalytic activity of ZnO nanorods on carbon fabrics, follows Langmuir-Hinshelwood kinetics. The study concludes that increase in the applied voltage significantly increases the rate of degradation of dyes by enhancing the photocatalytic activity of carbon fabrics containing ZnO nanorods. Graphical abstract: Image 1 Highlights: Growth of ZnO nanorods on carbon fabric. Effect of voltage on photocatalytic activity of nanorods treated carbon fabric. Enhanced photocatalytic dye degradation due to voltage.